OOCYTE CRYOPRESERVATION AND THE RELATED LEGISLATION IN THE CONTEMPORARY WORLD (Journal of Forensic Medicine & Toxicology, 2023)
In the contemporary world, where women are competing with men in all spheres of life, gone are the days when the only purpose in life for a woman was to procreate; today, they want to be successful in their professional life while balancing it with their personal life. Today’s career oriented women tend to postpone pregnancy to a later date which leads to age-related germ cell deterioration, and hence infertility which is where the concept of Oocyte Cryopreservation comes into the picture. Human Oocyte Cryopreservation is a procedure to preserve oocytes which can later be thawed, fertilized, and then, implanted as embryos in the uterus.
Keywords: ART(Assisted Reproductive Technology); Fertility; Medicolegal; Oocyte Cryopreservation; Pregnancy